Analisis Logam Berat Cd Dalam Alga Eucheuma cottoni Di Perairan Kabupaten Bantaeng - Teheni, Muhammad T.; La Nafie, Nursiah; Dali, Seniwati (Indonesian Journal of Chemical Research, 2016)
Algae is a plant which life in the marine with a lot of diversification such as: single and multi-cellular. Commonly, it contains chlorophyll without stem and roots. A species of algae in Indonesia which has high economic value is Eucheuma cottoni. It is cultured in Bantaeng as the central production of algae in South Sulawesi. The aim of this research is to know the concentration of heavy metals Cadmium in algae at region Bantaeng coastal. Concentration of cadmium was determined by atomic absorption spectrophotometer (AAS). This analysis was done by destruction process using concentrated HNO3. Sampling was done at 6 different location, they are: Nipa-nipa, Bakara, Boroloe, Tapaloe, Baruga village and Baruga from north to south. The experiment result show that the highest concentration of Cd is in Nipa-nipa village, with 0.2920 ppm and the lowest in Baruga village is 0.1824 ppm. The concentration of Cd in algae Eucheuma cottoni in those 6 different location had been more than limited which had been determined by the decision of national of environmental ministry number 51 year 2004, they are 0.01 and 0.05 ppm.